Adipofascial Flaps With Acellular Dermal Matrix Compared With Myocutaneous Flap Reconstruction in Lumbar Myelomeningocele Defects. Issue 5 (July 2018) - Pourtaheri, Navid; Wang, Derek; Calva, Daniel; Chopra, Karan; Kumar, Anand R.
Abstract : Background: Adipofascial flaps (AFF) with acellular dermal matrix (ADM) have the potential to reconstruct neural tube defects without sacrificing muscle that may be critical for long-term function. Comparative studies between myocutaneous flap (MF) reconstruction, the accepted standard reconstructive technique, and AFF/ADM remain under-reported. The aim of this study was to evaluate the safety and efficacy of myelomeningocele reconstruction using muscle sparing AFF/ADM versus MF. Methods: A retrospective comparison was conducted on consecutive myelomeningocele patients reconstructed with MF or AFF/ADM over an 84-month period. Data analyzed included: basic demographics, defect size, reconstructive technique, complications, and length of follow-up. A supplemental meta-analysis based on systematic review of literature was performed to compare alternative reconstructive options. Results: Twelve patients were identified who met inclusion criteria. Median age, weight, and defect size at reconstruction in the AFF/ADM group (n = 6) was 37.5 weeks, 3.25 kg, and 20.0 cm 2, respectively, and in the MF group (n = 6) was 37 weeks, 3.6 kg, and 22.5 cm 2 ( P  > 0.5). For the AFF/ADM versus MF groups, median follow-up was 33.8 versus 22.6 months, reoperation rate was 0% versus 17% ( P  = 1.0), and complex skin flap closure rate was 17% versus 100% ( P  = 0.015). No cerebrospinal fluid leaks or surgical site infections occurred in either group. Meta-analysis of the literature revealed no statistically significant difference in complications rates between muscle and nonmuscle flap reconstruction ( P  > 0.5); potential long-term sequelae of muscle flap harvest were not included. Conclusions: Muscle sparing AFF with ADM is a safe and effective surgical alternative to muscle flaps for lumbar myelomeningocele reconstruction.